Social participation of older adults in rural and urban areas: A cross-sectional survey in Turkey - EROL, SAİME (My University, 2023)
Social participation is important in terms of active aging and quality of life during old age. This cross-sectional study aimed to determine the social participation of older adults in rural and urban areas in Turkey. Related factors were similarly identified. The sample comprised 1,224 people over the age of 60, with a mean of 69.78 ± 7.48 years. Among the participants, 61.4% live in urban areas. The data were collected in family health centers through face-to-face interview and the Interview Form, Social Participation Assessment Form, and Social Participation Dimension of the Turkish Version of the Aging Module of the World Health Organization Quality of Life (WHOQOL) Scale. The scores obtained from the social participation dimension of the scale among the elderly in urban areas were higher than those obtained among the elderly in rural areas (p =.002). In addition, older adults in the urban areas who talked on the phone several times a month (p =.025), went to concerts, theater/cinema, museum/exhibition, various visual/musical shows (p =.046), and engaged in gardening (p =.032) obtained higher scores in the social participation dimension than the other participants. Health care professionals should take an advocacy role in building relationships with policy makers and create suitable socialization opportunities for older adults in urban and rural areas.
Keywords: Tıp; Sosyal ve Beşeri Bilimler; Sosyoloji; Demografi; Sağlık Bilimleri; Medicine; Social Sciences and Humanities; Sociology; Demography; Health Sciences; Klinik Tıp (MED); Sosyal Bilimler (SOC); Klinik Tıp; Sosyal Bilimler Genel; GERONTOLOJİ; DEMOGRAFİ; Clinical Medicine (MED); Social Sciences (SOC); CLINICAL MEDICINE; SOCIAL SCIENCES, GENERAL; GERONTOLOGY; DEMOGRAPHY; Sosyal Bilimler ve Beşeri Bilimler; Gerontoloji; Yaşam Boyu ve Yaşam Boyu Çalışmaları; Social Sciences & Humanities; Gerontology; Life-span and Life-course Studies; Older adults; social isolation; social participation